Appropriate Use Criteria for Hyaluronic Acid in the Treatment of Knee Osteoarthritis in the United States. (July 2017) - Bhadra, Arup K.; Altman, Roy; Dasa, Vinod; Myrick, Karen; Rosen, Jeffrey; Vad, Vijay; Vitanzo, Peter; Bruno, Michelle; Kleiner, Hillary; Just, Caryn
Objective: A workgroup of clinical experts has developed an Appropriate Use Criteria (AUC) for the use of hyaluronic acid (HA) in the treatment of osteoarthritis (OA) of the knee. The increasingly broad and varied use of HA injections, lack of published clinical guidance, and limited coverage for their use has created the imperative to establish appropriateness criteria. Methods: The experts of this workgroup represent rheumatology, orthopedic surgery, physiatry, sports medicine, and nursing clinicians with substantive knowledge of intra-articular HA therapy. This workgroup utilized the results of a systematic review of evidence, expert clinical opinion, and current evidence-based clinical practice guidelines to develop appropriateness criteria for the use of intra-articular HA for knee OA in 17 real-world clinical scenarios. Results: The workgroup scored the appropriateness of treatment of each patient scenario using a 9-point scale to designate a treatment as appropriate (7-9), uncertain (4-6), or inappropriate (1-3). Six scenarios were scored as appropriate, 10 scenarios were scored as uncertain, and 1 scenario was scored as inappropriate. Conclusion: This article can assist clinicians in shared decision-making by providing best practices in considering HA injections for knee OA treatment. Moreover, this AUC article can aid payers and policy makers in determining reimbursement and preauthorization policies and more appropriately managing health care resources. It is clear that further research is still necessary—particularly in patient populations differentiated by OA severity—that may benefit the greatest from the use of HA injections for the treatment of knee OA.